2017
DOI: 10.1089/hgtb.2016.158
|View full text |Cite
|
Sign up to set email alerts
|

AAVS1-Targeted Plasmid Integration in AAV Producer Cell Lines

Abstract: Adeno-associated virus (AAV) producer cell lines are created via transfection of HeLaS3 cells with a single plasmid containing three components (the vector sequence, the AAV rep and cap genes, and a selectable marker gene). As this plasmid contains both the cis (Rep binding sites) and trans (Rep protein encoded by the rep gene) elements required for site-specific integration, it was predicted that plasmid integration might occur within the AAVS1 locus on human chromosome 19 (chr19). The objective of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…We examined the electrophysiological properties from HEK cells transfected with the fPres-EGFP protein fusions by a site-specific gene transfer at the human AAV site 1 (AAVS1) [ 27 30 ]. Transgene expression is influenced by the integration site and some random insertions or transient transfections which can interfere with genes or disturb their transcription, while site-specific integration can minimize variations between different cells and constructs [ 31 , 32 ]. We chose the gerbil prestin as a positive control, while cells transfected only with the EGFP-vector were a negative control.…”
Section: Resultsmentioning
confidence: 99%
“…We examined the electrophysiological properties from HEK cells transfected with the fPres-EGFP protein fusions by a site-specific gene transfer at the human AAV site 1 (AAVS1) [ 27 30 ]. Transgene expression is influenced by the integration site and some random insertions or transient transfections which can interfere with genes or disturb their transcription, while site-specific integration can minimize variations between different cells and constructs [ 31 , 32 ]. We chose the gerbil prestin as a positive control, while cells transfected only with the EGFP-vector were a negative control.…”
Section: Resultsmentioning
confidence: 99%
“…Mammalian systems include human embryonic kidney (HEK)293 and HeLa cell lines [ 73 , 74 ]. In preclinical studies, adherent HEK293 cells are typically co-transfected with two or three plasmids, encoding the vector genome, rep and cap genes, and adenoviral helper genes.…”
Section: Aav Liver-directed Gene Therapy In Hemophilia Amentioning
confidence: 99%
“…Some common stable cell line strategies are summarized in Table 2. A stable producer cell line can be generated from the major production cell lines such as HEK293 (Abaandou et al, 2021; Selvaraj et al, 2021) and Sf9 (Joshi et al, 2019; Mietzsch et al, 2013), or less frequently reported HeLa (Luo et al, 2017) and A549 cells (Farson et al, 2004). Post GOI and rep/cap element integration, the rAAV production is initiated with the presence of a helper virus.…”
Section: Genetic Element Delivery To Host Cell Optimizationmentioning
confidence: 99%